2022
DOI: 10.1227/ons.0000000000000366
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Step 3-Dimensional-Navigated Single-Stage Lateral Surgery With Microtubular Decompression: A Case Series

Abstract: BACKGROUND:Single-stage lateral lumbar interbody fusion is a safe and effective procedure that relies on indirect decompression and fusion to treat various lumbar pathologies. This technique, however, has an overall 9% rate of indirect decompression failure, which may require additional surgery to achieve adequate direct decompression. To address this concern, we modified this technique by adding a minimally invasive, direct tubular decompression in lateral position when indicated. No study has described the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…We read with great interest the retrospective case series brought forth by the authors, 1 who should be commended for describing a small case series of lateral lumbar interbody fusion (LLIF) combined with minimally invasive direct microtubular decompression of the lumbar spine in a series of 7 patients with a median follow-up time of 1 year. The authors provided a detailed step-by-step explanation of the procedure and reported no cases requiring conversion to an open procedure, with only 1 revision (14.3%) occurring 20 months after the index procedure because of adjacent segment disease.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We read with great interest the retrospective case series brought forth by the authors, 1 who should be commended for describing a small case series of lateral lumbar interbody fusion (LLIF) combined with minimally invasive direct microtubular decompression of the lumbar spine in a series of 7 patients with a median follow-up time of 1 year. The authors provided a detailed step-by-step explanation of the procedure and reported no cases requiring conversion to an open procedure, with only 1 revision (14.3%) occurring 20 months after the index procedure because of adjacent segment disease.…”
mentioning
confidence: 99%
“…A special consideration was raised by the authors, 1 where the surgeon should be aware of the change in the surgical orientation while performing the microtubular decompression, traditionally performed on patients in prone position. Dealing with a different orientation further emphasizes the unfamiliarity of this procedure to surgeons, which might increase the risk of durotomy and prevent adequate dissection of the ligamentum flavum, and an adequate decompression of the ipsilateral lateral recess.…”
mentioning
confidence: 99%
See 1 more Smart Citation